Current situation of postharvest handling and fungal diseases of avocado ‘Hass’ for export in Michoacán, Mexico - Gonzalez, Juan Antonio Herrera; Baños, Silvia Bautista; Garcia, Samuel Salazar; Gutierrez Martinez, Porfirio (Revista Mexicana de Ciencias Agrícolas, 2020)
Mexico is the world’s leading producer and exporter of avocado ‘Hass’. Due to its nutritional characteristics in human health, the avocado ‘Hass’ has gained great popularity around the world. The objective of this review was to know the current state of avocado harvest and post-harvest management, as well as to review the infection process of the fungi Colletotrichum spp. and Lasiodiplodia theobromae, which cause the diseases called anthracnose and pedicle rot, respectively. These pathologies manifest themselves during postharvest maturation and storage. Currently, the main means of control of these microorganisms is a complex of the fungicides azoxystrobin + fludioxonil, the application of which is allowed only for exports to the United States of America. In Mexico, only the state of Michoacán can export avocado to the United States of America, but it seeks to increase exports to other international markets and integrate other producing regions, so it is necessary to look for alternatives to control postharvest diseases. Through the knowledge of the intrinsic protection mechanisms of the fruit, the bases could be laid to develop and evaluate new control models.